Development of a method to assess the dissolution of soft gelatin capsules containing progesterone in oily suspension - Diego R. Monterroza, Claudia M. Baena-Aristizábal, Luisa Fernanda Ponce D´león, Yolima Baena (Journal of Applied Pharmaceutical Science, 2024)
Progesterone is a class II active pharmaceutical ingredient according to the biopharmaceutics classification system, so its absorption is affected by solubility and dissolution rate. The work aimed to develop a dissolution method applicable to soft gelatin capsules of 100 and 200 mg of progesterone. Sink conditions were established based on solubility studies; the dissolution apparatus was selected, and the operational conditions of the method were established using an experimental statistical design. The established conditions were challenged in progesterone products, for which their result was already known from in vivo studies, with the same formulation but different particle size, to evaluate the discriminatory power of the method. The dissolution conditions selected were: United States pharmacopoeia apparatus 3, speed of 30 deeps per minute, dissolution media of 250 ml phosphate buffer solution at pH 6.8 with 4% sodium lauryl sulfate, 30 and 40 mesh at the top and bottom of the cell, respectively, and using a sinker for each capsule evaluated. The method proved to be discriminatory for the formulations studied. In addition to being functional for the evaluation of progesterone release at the product development stage, this method is also useful as a product quality control test.
Keywords: Progesterone, dissolution, soft gelatin capsule, biopharmaceutics classification system